Metal Coated Colloidosomes as Carriers for an Antibiotic - Sun, Qian; Zhao, Ziyan; Hall, Elizabeth A. H.; Routh, Alexander F. (Frontiers in Chemistry, 2018)
Colloidosomes are polymer shell microcapsules. They are stable and easy to prepare and have been used to encapsulate drugs for release at specific areas in the body. Traditional polymer shell capsules cannot totally seal drugs, since they are porous and small molecules diffuse through the polymer shell. In this paper, we report a method for encapsulating an antibiotic kanamycin using gold or silver coated colloidosomes. The colloidosomes are impermeable and can be triggered using ultrasound. To investigate the application of the capsules in a biological system, Escherichia Coli (E.coli) was chosen as a model organism. After triggering, the released antibiotic, as well as the metal shell fragments, kill E.coli. Both the silver and gold shells colloidosomes are toxic to this bacterial system and the gold coated colloidosomes can load a higher concentration of kanamycin.